Thiol‐functionalized fructose‐derived nanoporous carbon as a support for gold nanoparticles and its application for aerobic oxidation of alcohols in water. (5th June 2014) - Mahyari, Mojtaba; Shaabani, Ahmad; Behbahani, Mohammad; Bagheri, Akbar
<x xml:space="preserve">Abstract</x> Gold nanoparticles supported on thiol‐functionalized fructose‐derived nanoporous carbon (AuNPs@thiol‐Fru‐d‐NPS) were found to be a simple bench‐top, biocompatible, recyclable and selective catalytic system for the aerobic oxidation of various types of alcohols into their corresponding aldehydes and ketones at room temperature under the environmentally friendly conditions with excellent yields. Copyright © 2014 John Wiley & Sons, Ltd.